The small heat shock protein Hsp20.8 imparts tolerance to high temperatures in the leafminer fly, Liriomyza trifolii (Diptera: Agtomyzidae) - Zhang, Yue; Chang, Ya-Wen; Wang, Yu-Cheng; Yan, Yu-Qing; Du, Yu-Zhou (Bulletin of entomological research, 2024)
As an environmental factor, temperature impacts the distribution of species and influences interspecific competition. The molecular chaperones encoded by small heat shock proteins (sHsps) are essential for rapid, appropriate responses to environmental stress. This study focuses on Hsp20.8 , which encodes a temperature-responsive sHsp in Liriomyza trifolii , an insect pest that infests both agricultural and ornamental crops. Hsp20.8 expression was highest at 39℃ in L. trifolii pupae and adults, and expression levels were greater in pupae than in adults. Recombinant Hsp20.8 was expressed in Escherichia coli and conferred a higher survival rate than the empty vector to bacterial cells exposed to heat stress. RNA interference experiments were conducted using L. trifolii adults and prepupae and the knockdown of Hsp20.8 expression increased mortality in L. trifolii during heat stress. The results expand our understanding of sHsp function in Liriomyza spp. and the ongoing adaptation of this pest to climate change. In addition, this study is also important for predicting the distribution of invasive species and proposing new prevention and control strategies based on temperature adaptation.